2020
DOI: 10.4995/wrs.2020.12216
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of acid-insoluble ash as internal marker for the measurement of digestibility in rabbits

Abstract: <p>The present study aimed to evaluate acid-insoluble ash (AIA) as an internal marker for the measurement the coefficient of total tract apparent digestibility (CTTAD) in rabbits through two experiments (E1 and E2). In E1, 48 rabbits were used to calculate the CTTAD of the same basal diet according to the European reference method (ERM), the AIA and the titanium dioxide (TiO<sub>2</sub> with 1 g of TiO<sub>2</sub>/kg diet) techniques (n=16 rabbits/method). The effect of feed sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…With respect to using rabbits in digestion studies, these results caution against the use of acid insoluble ash as a digestibility marker (Papadomichelakis & Fegeros, 2020) in animals that had previous access to soil or soil-contaminated diets, or against diets that contain substances that might be sequestered by the 'wash-back' colonic separation mechanism. Nevertheless, the observation that the vast majority of the 14-day silica intake (app.…”
Section: Discussionmentioning
confidence: 98%
“…With respect to using rabbits in digestion studies, these results caution against the use of acid insoluble ash as a digestibility marker (Papadomichelakis & Fegeros, 2020) in animals that had previous access to soil or soil-contaminated diets, or against diets that contain substances that might be sequestered by the 'wash-back' colonic separation mechanism. Nevertheless, the observation that the vast majority of the 14-day silica intake (app.…”
Section: Discussionmentioning
confidence: 98%
“…Later, laboratory DM was estimated by keeping powdered faecal samples at 105 • C for 3 h according to AFIA [28] protocol. The total tract apparent DM and OM digestibility were determined using the acid insoluble ash [29] technique developed by Van Keulen and Young [30] with slight modifications [31,32]. The NDF [5] and ADF were determined according to the method described by ANKOM technology using an ANKOM2000 Fiber Analyzer (ANKOM Technology, New York, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Acid insoluble ash could be used as an internal marker to calculate the digestibility of a diet precisely, and the method could be used as an alternative to total collection method in many animals (Figueiredo et al, 2019;Papadomichelakis & Fegeros, 2020). However, Prawirodigdo, Gannon, Leury and Dunshea (2021) demonstrated that the basal diet and choice of indigestible marker can substantially influence the determination of apparent total tract digestibility and that the use of AIA as an indigestible marker varies with species of animal used.…”
mentioning
confidence: 99%